Study of the clinical profile of community-acquired pneumonia: a cross-sectional study in northeast India - Annu Gupta; KG Lynrah; Monaliza Lyngdoh; Iadarilang Tiewsoh; Baphiralyn Wankhar; Debashis Priyadarshan Sahoo; Bhupen Barman; Mohammad Jamil; Gwenette Andrea War (Monaldi Archives for Chest Disease)
Community-acquired pneumonia (CAP) continues to pose a significant public health burden in India, particularly in the northeastern region, where data on microbial etiology and resistance patterns remain scarce. This cross-sectional observational analytical study, conducted over one year at a tertiary care center in northeast India, analyzed 117 adult patients with clinico-radiologically confirmed CAP to elucidate their clinical, epidemiological, and microbiological profiles. The cohort was predominantly male (76.9%), with a mean age of 52 years, and the most affected age group was 31-40 years. Hypertension and chronic obstructive pulmonary disease were the most common comorbidities. Cough, breathlessness, and fever were the leading symptoms. Sputum cultures were positive in 42.7% of cases, with a striking predominance of gram-negative organisms (94%), especially Klebsiella pneumoniae and Pseudomonas species. Alarmingly, high resistance rates were observed for widely used antibiotics such as ceftriaxone and cefuroxime, while meropenem, amikacin, and ertapenem retained high sensitivity. These findings emphasize the critical need for tailored, region-specific empirical treatment strategies in light of emerging antibiotic resistance trends in CAP.